1999
DOI: 10.1161/01.str.30.9.1844
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Diaschisis in Stroke Recovery

Abstract: Background and Purpose-Recovery from hemiparesis after stroke has been shown to involve reorganization in motor and premotor cortical areas. However, whether poststroke recovery also depends on changes in remote brain structures, ie, diaschisis, is as yet unresolved. To address this question, we studied regional cerebral blood flow in 7 patients (meanϮSD age, 54Ϯ8 years) after their first hemiparetic stroke. Methods-We analyzed imaging data voxel by voxel using a principal component analysis by which coherent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
105
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(111 citation statements)
references
References 79 publications
3
105
0
2
Order By: Relevance
“…Several previous studies have suggested that CCD is not only an important prognostic factor for stroke recovery but is also associated with cognitive function and the development of vascular dementia. 10,13,[33][34][35] Therefore, the quantification of CCD can be used as a clinical prognostic indicator. However, few studies have reported a correlation between the clinical outcome and treatment response in patients and the quantitative value of CCD.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have suggested that CCD is not only an important prognostic factor for stroke recovery but is also associated with cognitive function and the development of vascular dementia. 10,13,[33][34][35] Therefore, the quantification of CCD can be used as a clinical prognostic indicator. However, few studies have reported a correlation between the clinical outcome and treatment response in patients and the quantitative value of CCD.…”
Section: Discussionmentioning
confidence: 99%
“…Because Rosa et al (2000) studied MT neurons weeks after V1 lesions, they suggested that total deactivation obtained immediately after the lesions by Kaas and Krubitzer (1992) could be attributable to a widespread depression that might follow a lesion (Seitz et al, 1999). This explanation seems unlikely, given that there were normal responses in portions of MT outside the deprived zone in the study of Kaas and Krubitzer (1992).…”
Section: Discussionmentioning
confidence: 99%
“…39 Imaging studies in stroke patients have shown diaschisis in cerebellar structures in the motor domain 40 -44 and also in other regions related to language 45 and vision 46 processing. Resolution of cerebellar diaschisis has been proposed as one of the mechanisms contributing to recovery of motor function after stroke; 47,48 for example, after intake of amphetamines.…”
Section: Diaschisismentioning
confidence: 99%